ANALISIS TOTAL FENOLIK DAUN GEDI HIJAU (Abelmoschus manihot L.) DENGAN MENGGUNAKAN SPEKTROSKOPI FTIR DAN KEMOMETRIK - Rumoroy, Jhon D.; Sudewi, Sri; Siampa, Jainer P. (PHARMACON, 2019)
ABSTRACTNatural phenolic compounds, including organic compounds, is the natural substances that produced by organisms. This study aims to determine the total phenol content and optimization using the FTIR method for rapid phenols analysis. Gallic acid was used as a comparison standard to measure the total phenol content using a UV-Vis spectrophotometer. The calorimetric method was used to determine the total Phenolic content of the Green Gedi Leaf extracts in 8 samples of growing sites, namely Minahasa 855.8 µg GEA / g extract ± 0.033, Southeast Minahasa 283.7 µg GEA / g extract ± 0.006, Manado 580.2 µg GEA / g extract ± 0.012, North Minahasa 716.2 µg GEA / g extract ± 0.091, Kotamobagu 793 µg GEA / g extract ± 0.03, Minahasa Selatan 290.6 µg GEA / g extract ± 0.027, Bitung 365.6 µg GEA / g extract ± 0.035, Tomohon as much as 546.5 µg GEA / g extract ± 0.003. This result involves a combination of variables x (FTIR measurement results) and y variables (data from the analysis of Folin-Ciocalteu). Error value (standard error calibration (SEC = 0.003), standard error of prediction (SEP = 0.042)) and calibration r value 0.999 and r validation 0.98. Keywords: Green Gedi Leaves, UV-Vis Spectrophotometer, Kemometrics, Phenol Total, FTIR Spectrophotometry.ABSTRAK Senyawa fenolik alam termasuk senyawa organik bahan alam yang dihasilkan oleh organisme. Penelitian ini bertujuan untuk mengetahui kandungan fenol total Daun Gedi Hijau dan optimasi menggunakan metode FTIR untuk analisis fenolsecara cepat. Asam  galat digunakan standar pembanding dalam mengukur kandungan total fenol menggunakan spektrofotometer UV-Vis. Metode kemometrik digunakan untuk mengetahui kandungan Total Fenolik pada ekstrak Daun Gedi Hijau pada 8 sampel tempat tumbuh yaitu Minahasa 855,8 µg GEA/g  ekstrak ± 0,033, Minahasa Tenggara 283,7 µg GEA/g  ektrak ± 0,006, Manado 580,2 µg GEA/g  ekstrak ± 0,012, Minahasa Utara 716,2 µg GEA/g  ekstrak ± 0,091, Kotamobagu 793 µg GEA/g  ekstrak ± 0,03, Minahasa Selatan 290,6 µg GEA/g  ekstrak ± 0,027, Bitung 365,6 µg GEA/g  ekstrak ± 0.035, Tomohon sebesar 546,5 µg GEA/g  ekstrak ± 0,003. Hasil ini melibatkan kombinasi variable x (hasil pengukuran FTIR) dan variable y (data hasil analisis Folin-Ciocalteu). Nilai kesalahan (standard error calibration (SEC = 0.003), standard error of prediction (SEP = 0.042)) dan nilai r kalibrasi 0,999 serta  r validasi 0,98. Kata Kunci: Daun Gedi Hijau, Spektrofotometer UV-Vis, Kemometrik, Total Fenol, Spektrofotometri FTIR.